Factors Influencing Intention to Use Mobile Learning: A Quantitative Study in Higher Education - Baso Intang Sappaile; Hendro Sukoco (Scientechno: Journal of Science and Technology, 2024)
In this modern era, the use of technology is increasingly widespread among students at universities. One of them is the increasing use of mobile technology in learning, showing the importance of understanding the factors that influence the intention to use mobile learning among students. The aim of this research is to determine and analyze the factors that influence the intention to use mobile learning among college students. Apart from that, it is also to find out the relationship between the variables studied. This research method uses a quantitative method with a questionnaire as a data collection instrument. The research sample consisted of students at universities who used mobile learning in the learning process. The results of this research indicate that there are several factors that influence the intention to use mobile learning in higher education, including ease of use, perceived benefits, perceptions of usefulness, and social factors. These variables make a significant contribution to the intention to use mobile learning among students. The conclusion of this study confirms that factors such as ease of use, perceived usefulness, perception of usefulness, and social factors play an important role in forming intentions to use mobile learning in higher education environments. The implication of this research is the importance of integrating these factors in the development of effective learning strategies using mobile technology to increase student participation and performance in higher learning. The limitation of this research is that the researcher did not directly conduct research at universities, but by distributing questionnaires to students at universities.